Algae- and bacteria-based biodegradation of phthalic acid esters towards the sustainable green solution - Amirian, Veghar; Russel, Mohammad; Yusof, Zetty Norhana Balia; Chen, Jit Ern; Movafeghi, Ali; Kosari-Nasab, Morteza; Zhang, Dayong; Szpyrka, Ewa (Springer Science and Business Media B.V., 2025)
Phthalic acid esters are widely used worldwide as plasticizers. The high consumption of phthalates in China makes it the world’s largest plasticizer market. The lack of phthalic acid ester’s chemical bonding with the polymer matrix facilitates their detachment from plastic products and subsequent release into the environment and causes serious threats to the health of living organisms. Thus, environmentally friendly and sustainable solutions for their removal are urgently needed. In this context, both natural and engineered bacterial and algal communities have played a crucial role in the degradation of various phthalic acid esters present in water and soil. When algae-bacteria co-culture is compared to a singular algae or bacteria system, this symbiotic system shows superior performance in the removal of dibutyl phthalates and diethyl phthalates from synthetic wastewater. This review provides an optimistic outlook for co-culture systems by in-depth examining single microorganisms, namely bacteria and algae, as well as algae-bacterial consortiums for phthalates degradation, which will draw attention to species co-existence for the removal of various pollutants from the environment. In addition, further development and research, particularly on the mechanisms, genes involved in the degradation of phthalic acid esters, and interactions between bacterial and algal species, will lead to the discovery of more adaptable species as well as the production of targeted species to address the environmental pollution crisis and provide a green, efficient, and sustainable approach to environmental protection. Discrepancies in knowledge and potential avenues for exploration will enhance the existing body of literature, enabling researchers to investigate this field more comprehensively.